UJI KETAHANAN GALUR-GALUR KENTANG TRANSGENIK HASIL TRANSFORMASI DENGAN GEN RB TERHADAP PENYAKIT HAWAR DAUN (PHYTOPHTHORA INFESTANS) DI KP PASIRSARONGGE, CIANJUR - Edy Listanto; M . Herman; Eri Sofiari (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2013)
Resistance test strains of transgenic potatoes transformed with RB gene to late blight (Phytophthora infestan) in KP Pasirsarongge, Cianjur. Potato late blight caused by Phytophthora infestans (P. infestans) (Mönt.) de Barry continues to be one of the most important crop diseases of all time. Genetic engineering of potato using RB gene for resistant plant to this disease is the most effective and environmental friendly to prevent widespread of late blight. This research aims to perform resistance of transgenic potato lines containing RB gene to lateblight (P. infestans) in Pasirsarongge, Cianjur field trial station. The first generation of transgenic lines were planted on polybag containing soil:manures using randomized complete block design. Tested plant inoculation was done naturaly from inoculum source from border row (Granola) that has been planted at one month before. The symptom was observed at one month after planting and damage scoring was done every three days for five times. Twenty two transgenic lines of tested plant showed various resistance respond to late blight (P. infestans) attack. Three transgenic lines showed highly resistance to late blight (P. infestans) were lines 11, 24, and 25, one transgenic line has resistant level was line 6.